Penerapan Program Linear untuk Mengoptimalkan Jumlah Produksi dalam Memperoleh Keuntungan Maksimal pada Rumah UMKM Produk Wedang Sehat - Zulkarnain, Aulia; Prakoso, Bagus Aji; Dewi, Rahayu Kusnita; Rahmawati, Rani; Bilatasya, Yolanda (Indo-MathEdu Intellectuals Journal, 2024)
Linear programming is a mathematical method used to solve problems related to linear optimization (maximum value and minimum value). Quoted from Mathematics 3 competency by Johanes, linear programming is a part of mathematics in the form of models, which consist of linear inequalities as a method for solving various problems in everyday life. This linear program can help solve problems ranging from basic to complex. This article aims to apply the use of linear programming in determining the maximum profit that can be obtained for managers of healthy wedang products. In this case, traders of ginger wedang products can use linear programming using the simplex method to find maximum profits manually and analyze using POM-QM for Windows software. The results of the analysis using the linear program of the simplex method with calculations on POM-QM have the same results, namely the maximum profit of MSME houses wedang sehat buk Sumiati in one day reaches Rp. 180,000 by producing healthy wedang ginger powder (X1) as much as 1 piece and wedang sehat suetajarah (X2) as much as 1 piece.